ANALISIS DAN SIMULASI KONVERTER DC-DC PENAIK TEGANGAN DENGAN CELL PENGUAT TINGGI UNTUK APLIKASI PHOTO VOLTAIC (PV) - Anung -; Givy Devira Ramady; Purwadi Budi Santoso; Taufik Rachman; Yakob liklikwatil; Dwiyanto - (Power Elektronik : Jurnal Orang Elektro, 2023)
The range of DC output voltage of the photovoltaic cell is about 20 - 45 Vdc. At generally electrical load use an AC voltage is about 220 Vac for one phase load and a 380 Vac for three phase load. So that the output voltage of the photovoltaic cell has to raise up to 400 Vdc and then it voltage changed to an AC voltage with an inverter. In this paper, the voltage conversion ratio of the DC to DC voltage with high gain cell power converter will be analyzed and simulated with PSIM software. From the analysis and simulations show that the output voltage of that converter can be achieved it about 400 Vdc from around input voltage 20 Vdc, the duty cycle of the semiconductor switch is 71 %.